Cluster policy in the light of institutional context: a comparative study of transition countries - Lehmann, Tine; Benner, Maximilian (Administrative Sciences, 2015)
The business environment in transition countries is often extraordinarily challenging for companies. The transition process these countries find themselves in leads to constant changes in the institutional environment. Hence, institutional voids prevail. These institutional voids cause competitive disadvantages for small and medium enterprises. Cluster policy can address these competitive disadvantages. As cluster policy generally aims at supporting companies' competitive advantage by spurring innovation and productivity, it can help to bridge institutional voids. This article's research question aims at analyzing and comparing cluster policies in the institutional context of two transition countries (Serbia and Tunisia) and analyzes to what extent cluster policies in these two countries are adapted to institutional voids prevailing there. The case studies offer insights into apparent difficulties of clusters in bridging formal institutional voids, as well as, notably, into the informal void of skill mismatches in the labor market. Still, for some specific voids, clusters do at least implicitly assume a bridging role. While the cluster policies examined do not explicitly target the institutional voids identified, cluster management can-in the course of time-align its service offering more closely with these voids. Bottom-up designed cluster policies can play an especially important role in such an evolution towards bridging institutional voids.